Evaluation of Four Bait Traps for Sampling Wireworm (Coleoptera: Elateridae) Infesting Cereal Crops in Montana. (7th June 2017) - Morales-Rodriguez, Anuar; Ospina, Aracely; Wanner, Kevin W
The basic principles of a reliable integrated pest management program include pest identification, monitoring, and distribution. Selecting the appropriate sampling protocol to monitor wireworm for research or applied entomology depends on the objective, including simply detecting the presence or absence of wireworm, surveying the composition of wireworm assemblages, or estimating spatial and temporal population densities. In this study, the efficacy of pitfall, stocking, pot, and canister traps baited with wheat and barley mixtures was evaluated for monitoring wireworm populations in four commercial cereal fields in Montana. Pitfall and stocking traps collected greater numbers of wireworm (1625 and 1575, respectively) followed by pot-type and canister-type traps (1173 and 725, respectively). The 5098 wireworm collected from four sites included seven species: Aeolus mellillus, Agriotes sp, Dalopius sp, Hypnoidus bicolor, Limonius californicus, Limonius infuscatus, and S. aeripennis .